Knowledge Level of COVID-19 Prevention in Banjar Gambang Communities, Seraya Village, Karangasem, Indonesia - Sasmana, I Gede Aswin Parisya; Wihandani, Desak Made; Halim, Wilson; Jaya, Ni Komang Ayu Amanda Setiari; Atmaja, Made Ayu Kurniati; Edgar, Christine; Sutedja, Jane Carissa; Mamangdean, Christo Timothy; Wijaya, Grace Veronika; Kusumadewi, Made Dea Avrilia (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: Problems to COVID-19 are closely related to the level of knowledge and community prevention. Therefore, to overcome COVID-19, increased knowledge and prevention are needed. This study aimed to evaluate the correlation between prevention and knowledge level about COVID-19.Methods: A cross-sectional study using a convenience sampling approach was conducted in Banjar Gambang, Karangasem, Indonesia, in April 2022. The knowledge level and preventive behavior towards COVID-19 were measured using the COVID-19 Preventive Behaviors Index (CPBI) and the knowledge, attitudes, and practice toward COVID-19 (KAPCOV-19) questionnaire. The data were analyzed using SPSS software version 26.0.Results: A total of 52 respondents were included, who had excellent level of knowledge (44.2%) and moderate prevention behaviour (48.1%). A strong and significant correlation was found between the preventive index and the knowledge levels of COVID-19 (r = 0.548; p<0.001). The level of knowledge was significantly related to the level of preventive behavior (p= 0.003), as well as the education level (r = 0.323; p = 0.02) and age (r= -0.346; p=0.012).Conclusion: The level of knowledge and the individual prevention behavior toward COVID-19 are directly proportional to each other. Those who have a low level of knowledge, might affect their prevention behavior toward COVID-19, therefore, personalized socialization of COVID-19 prevention is still required.